International financial inclusion: some multidimensional determinants - Lilianne Isabel Pavoń Cueĺlar (Small Business International Review (SBIR), 2018)
The generalized access to financial services is a promising source of growth and social inclusion to reach "decent life for all", just as is conceived in the development agenda in the Millennium Declaration and ratified in the 2030 agenda for sustainable development of the United Nations. Some groups in financial terms are more excluded than others: the poor, women, youngsters, and the inhabitants of far rural communities scarcely populated, tend to face a larger number of barriers to access these services. Recently created businesses and small ones face a greater number of insuperable obstacles. This paper analyzes the recent financial inclusion in the global scope, with special emphasis on SMEs. Its importance and meaning are deeply examined; some of its determinants are presented and tested, such as credit banking, through a model based on panel data. It is found that, given some country cultural traits linked to their risk aversion and long-term vision, achieving a larger financial inclusion on the credit side, depends not only on the access channels and the characteristics of the offered products, but on different demand aspects as some socioeconomic features of their potential customers. – – El acceso generalizado a servicios financieros constituye una fuente de crecimiento e inclusioń social prometedora para alcanzar "una vida digna para todos", tal y como se concibe en la agenda para el desarrollo en la Declaracioń del Milenio y ratificada en la agenda 2030 para el desarrollo sostenible de las Naciones Unidas. Algunos grupos estań maś excluidos que otros en teŕminos financieros: los pobres, las mujeres, los jov́enes y los habitantes de zonas rurales remotas y poco pobladas, suelen afrontar obstaćulos mayores para acceder a servicios de esta naturaleza. Entre las empresas, las recientes y las pequen\~as enfrentan un mayor nuḿero de obstaćulos insalvables. Este trabajo analiza la inclusioń financiera reciente en el aḿbito mundial, con un especial eńfasis en las PyMEs. Se profundiza en su importancia y significado, para despueś presentar algunos de sus determinantes y someterlos a prueba para el caso del cred́ito bancario, mediante un modelo con datos panel. Se encuentra que, dados ciertos rasgos culturales del paiś vinculados a su aversioń al riesgo y visioń de largo plazo, lograr un mayor nuḿero de prestatarios del sistema bancario depende de los canales de acceso y de los atributos de los productos que este ofrece, pero tambień de aspectos de demanda como son ciertas caracteriśticas socioeconoḿicas de sus clientes potenciales.
Keywords: G21; M20; 650; Financial inclusion; cultural traits; SMEs; credit; inclusioń financiera; cultura; PyMEs; financiacioń